The Identification of Spanish Women with Advertisements in High-End Magazines - Vega Saldaña, Silvia Mª; Barredo Ibáñez, Daniel; Merchán Clavellino, Ana (Comunicación y Género [Communication and Gender], 2020)
This study investigates the perception that the female population possesses about the corporal pattern prevailing in the advertising of Spanish high-end women’s magazines. Among the results obtained, it has been found that this sector enhances in its advertising pages models that exhibit restrictive corporal patterns, PCE, which are established as a paradigm of the female corporeal ideal to which the current woman should aspire. A PCE settled on the following parameters: height ≤36, height ≥170 centimeters and somatotype ectomorfo, and to which are associated corporal attributes that make reference to the white ethnic group, clear tones in eyes and hair, a long mane, eternal youth and corporeal perfection.